Place-Based Inquiry Teaching Approach (PBITA): Effects on Junior High School Students’ Conceptual Understanding in Biology - Macaumbao, Sittie Ainah B.; Abdulmalik, Hannah P. (Education, Science, and Technology International Conference, 2025)
This study examined the effects of the Place-based Inquiry Teaching Approach on Grade 8 students’ conceptual understanding in Biology. Using a quasi-experimental design, two (2) sections of students from MSU-Tamparan Community High School during the school year 2024–2025 school year participated. Data were collected through a researcher-made Biology Conceptual Understanding Test (BCUT) with a reliability coefficient of 0.82. Analysis included descriptive statistics, independent samples t-test, and Levene’s test at a 0.05 significance level. Specifically, the study investigated: (1) students’ conceptual understanding levels in both experimental and control groups before and after the intervention; (2) significant difference between the mean scores of the experimental and the control group in their conceptual understanding test before and after the intervention and their mean gain score; and (3) the experimental group’s perceptions of the Place-based Inquiry Teaching Approach. Findings revealed that after the intervention, 93.3% of students in the experimental group reached the "Developed" level of conceptual understanding compared to 46.7% in the control group. The experimental group had a significantly higher mean BCUT score (39.20) than the control group (28.27), with mean gains of 18.00 and 7.87, respectively (p = 0.000). Thematic analysis of student reflections and interviews revealed positive perceptions of the teaching approach, emphasizing its engaging and meaningful nature through real-life applications, local context exploration, and collaborative learning.